The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1247/csf.10003
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Tube Guidance by Attractant Molecules: LUREs

Abstract: ABSTRACT. Sexual reproduction in flowering plants requires pollen-tube guidance, which is thought to be mediated by chemoattractants derived from target ovules. To date, however, no convincing evidence has been reported of a particular molecule being the true attractant. Emerging data indicate that two synergid cells, which are on either side of the egg cell, emit a diffusible, species-specific signal to attract the pollen tube at the last step of pollen-tube guidance. Recently, it was demonstrated that LUREs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Thus, in total, three different sets of DEFL genes were found, each overrepresented among the transcripts showing that expression character: ES-enriched; MPenriched; and dual gametophyte-enriched. Some members of this family have previously been shown to be expressed in synergids in maize and to function as pollen tube attractants in Torenia [28,[44][45][46][47].…”
Section: Gene Ontology Functional Category Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in total, three different sets of DEFL genes were found, each overrepresented among the transcripts showing that expression character: ES-enriched; MPenriched; and dual gametophyte-enriched. Some members of this family have previously been shown to be expressed in synergids in maize and to function as pollen tube attractants in Torenia [28,[44][45][46][47].…”
Section: Gene Ontology Functional Category Enrichmentmentioning
confidence: 99%
“…Characterization focused on two families with known gametophyte members: DEFENSIN/LURE (DEFL) [44], and Zm Egg Apparatus1 (ZMEA1)-LIKE (EAL) [58][59][60][61]; and two families that had not previously been shown to have gametophyte-expressed members, CLAVATA3-ESR (CLE) [62], and LITTLE ZIPPER (ZPR) [63] (Figures 5 and 6; Additional files 17 and 18).…”
Section: Analysis Of Small Peptide Gene Family Expressionmentioning
confidence: 99%
“…In this system, it was unambiguously shown that the synergids produce pollen tube attractants (Higashiyama et al, 2001). Recently, the Torenia LURE proteins, secreted cysteine-rich peptides that accumulate in the filiform apparatus of the synergid cells, have been identified as pollen tube attractants (Okuda et al, 2009;Okuda and Higashiyama, 2010). In Arabidopsis, synergids and other embryo sac cells produce a diverse set of cysteine-rich proteins (Jones-Rhoades et al, 2007;Dresselhaus and Márton, 2009;Wuest et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple signaling events have to occur successfully after pollination before the pollen tube can finally join the female gametophyte (Lausser and Dresselhaus 2010;Marton and Dresselhaus 2010;Okuda and Higashiyama 2010). Double fertilization results in two individual fertilization products: the diploid zygote that will develop into the embryo and the triploid nutritive tissue of the endosperm.…”
Section: Cell Death Decisions During Fertilization and Seed Developmentmentioning
confidence: 99%